P9 Early identification of risk for fetal alcohol spectrum disorders: A systematic review of biomarkers of prenatal alcohol exposure. (27th April 2016) - McQuire, C; Paranjothy, S; Hurt, L; Mann, M; Farewell, D; Kemp, A
Abstract : Aim: Diagnosis of fetal alcohol spectrum disorders (FASD) is often complicated by missing or unreliable information about alcohol exposure in-utero. Objective measurement of prenatal alcohol exposure is essential for identifying children at risk of FASD to support diagnosis and early intervention. Biomarkers have been advocated for use in population based screening programmes and feature as a recommended method within the Canadian National Screening Toolkit for FASD. However, their validity has not been comprehensively evaluated. This study aimed to systematically review the validity of objective measures of prenatal alcohol exposure. Methods: We searched 13 electronic databases and supplementary sources to identify relevant studies published between January 1990 and October 2015. Eligible studies provided data about the validity of biomarkers within maternal and neonatal biological matrices for the detection of prenatal alcohol exposure. We excluded animal studies and non-English language publications. Methodological quality was assessed using the Quality Assessment of Diagnostic Accuracy Studies tool (QUADAS-2) and evidence was synthesised using narrative analysis. Results: Twelve studies met inclusion criteria. Most (8) studies investigated objective measures of heavy prenatal alcohol exposure and included pregnant women and neonates from high risk settings, such as substance misuse clinics. Test performance varied widely for biomarkers in meconium (7 studies, sensitivity 4% to 100%, specificity 13% to 98%), maternal blood (4 studies, sensitivity 0% to 100%, specificity 79% to 100%), maternal hair (2 studies, sensitivity 19% to 85%, specificity 79% to 86%) maternal urine (2 studies, sensitivity 15%, specificity 97% to 100%) and biomarker test batteries (2 studies sensitivity 22% to 50%, specificity 56% to 97%). Placental biomarkers demonstrated 82% sensitivity and 83% to 94% specificity in one study. Selected outcomes are presented in Figure 1 . Methodological quality assessment suggested a high risk of bias within included studies due to the use of self-report reference standards and selective outcome reporting (Figure 2 ). Conclusions: Current evidence is insufficient to support the use of objective measures for prenatal alcohol exposure screening in practice. Biomarkers in meconium and placental tissue may be the most promising candidates for future research and require validation in population based studies.